Análise da suscetibilidade a corridas de massa aplicada a dutovias: estudo de caso na bacia do Ribeirão do Roque - Lumiatti, Gabriela [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This scientific research aimed at to analyse the susceptibility to debris flow of the watershed of Ribeirão do Roque (SP), focusing on the upstream areas of OSBRA pipeline. This is because, mass flow can cause damage to pipes, mainly due to conditioning hydro erosion of the land in the drainage crossings, including the undermining the banks of streams. Firstly, It was conducted a literature review, aiming to identify and understand the principal characteristics and conditions of debris flow. Secondly, the physical and anthropic factors and their respective weights of influence were selected and used to determine the mass flow susceptibility. It was selected the following physical factors: type and thickness of rocks, soil and unconsolidated materials; textural density; amplitude relief; relief slope; shaped valley; and shape of slopes. Such factors are present in the physiographic subdivision map of the study area. In addition, the anthropic attributes correspond to the classes contained in the land use map. Therefore, the physical and anthropic factors were integrated through the multi-criteria analysis in a GIS environment, generating a total susceptibility map of debris flow on the scale 1:50,000. The results showed that a significative part of the study area was classified as average susceptibility. However, it was identified areas with high susceptibility in the region in which the pipe cross the Ribeirão do Roque. Moreover, at which point the river presents a closed valley and a meander shape, without a fluvial plain that would be useful to attenuate the development of the process. Consequently, if a mass flow begins in any of these most susceptible regions located upstream of the pipe, the chances that the process develops by the river and causes the excavations of his bed are quite large. However, the pipelines cross these critical areas directly on the rock (diabase), which provides additional protection against possible ...

O presente Trabalho de Conclusão de Curso teve como objetivo analisar a suscetibilidade a corridas de massa da Bacia do Ribeirão do Roque, com enfoque nas áreas situadas a montante do duto OSBRA (Oleoduto São Paulo- Brasília). Uma vez que, corridas de massa/detritos podem afetar sistemas de dutos, principalmente, condicionando erosão hídrica dos terrenos em travessias de drenagens, incluindo solapamento de margens de córregos. Primeiramente foi realizado um levantamento bibliográfico, a fim de que as principais características e condicionantes do processo de corridas pudessem ser identificados e compreendidos. A partir destas informações, foram selecionados os fatores físicos e antrópicos e seus respectivos pesos utilizados na determinação da suscetibilidade a corridas de massa, de acordo com sua influência na geração do processo. Os fatores físicos utilizados foram: tipo e espessura das rochas, solo e materiais inconsolidados; densidade textural; amplitude do relevo; declividade do relevo; forma de vale; e forma de encostas. Tais fatores estão contidos no mapa de compartimentação fisiográfica da área de estudo. Além disso, os atributos antrópicos correspondem as classes contidas no mapa de uso e ocupação do solo. Sendo assim, por meio da análise multicriterial em ambiente SIG, integraram-se os atributos físicos e antrópicos, gerando um mapa de suscetibilidade total a corridas de massa na escala 1:50.000. Os resultados mostraram que a maior parte da bacia apresentou média suscetibilidade a corridas, sendo que especificamente na região na qual o duto atravessa o Ribeirão do Roque, localizam-se áreas classificadas como alta suscetibilidade, sendo que neste ponto o rio apresenta um vale mais fechado e encontra-se na forma de meandro, sem a existência de planície aluvionar, capaz de amortecer as corridas. Consequentemente, caso uma corrida se inicie em alguma destas regiões mais suscetíveis, localizadas a...
Keywords: Geologia de engenharia; Deslizamentos (Geologia); Roque, Ribeirão do (SP)